FEATURES OF MODERN APPROACHES TO TEACHING PRIMARY SCHOOL SUBJECTS - Onaxon Mannapovna Jabborova; Durdonaxon Toshtemirova (European Science Publishing, 2024)
The article reflects on the problem of modern approaches to teaching subjects in elementary school and presents the authors' approaches.
Keywords: Elementary school, academic subjects, the learning process, modern approaches, methodological analysis, diagnosis, knowledge, skills, qualifications.